Espaço urbano e subversão pela existência corporificada Queer em Uberlândia/MG - Mota, Cássio Henrique Naves (2019)
This research has the meaning of comprehending urban space by the subverted logic of queer experiences in Uberlândia/MG, especially those that spatialized in Rosários square centrality, in Fundinho. The city that we live today is produced and planned by social elites that keep economic power in their hands and creates from ideologies, standards to be followed by the rest of the population to achieve that the control is effective and power is granted. These powers can be represented by rich, white, heterosexual, cisgender men that uses neutrality discourses in architecture to build discipline and surveillance spaces. The brazilian city is built this way since its first settlements, like Uberlândia/MG, that since recognized as a city deals with spatial appropriation conflicts between marginalized communities and the elite. Minorities like black people and prostitutes suffer with the making of segregated spaces and fight back taking city spaces while they can to show their needs and cultural intentions. Power, then, has traces of misogyny and patriarchalism that echoes on society and spatial production, taking example from queer bodies that since Brazils colonization have suffered with control mechanisms created to restrain their spatial expressions. After the Stonewall riot and the first Pride Parades, it’s possible to perceive the uprising of new queer spaces that are studied here nowadays. Spaces such as clubs, saunas, dark rooms, cruising spaces that are taken to perform dissidents sociabilities in Uberlândias central area, especially by gay men, showing how consumption and the hegemonic power can reverse the way theses spaces are subverted. Spaces to bodies out of the closet, made for fighting to equality or anonymous ones, appropriated by queer groups and their logic. By spatial analysis and ethnographic writing from some central spaces near Rosários square, it’s possible to perceive that even those subverted spaces are mostly masculine and eases men dynamics, regardless the sexuality. This shows the importance of studying how these occupancies show up, who are their social actors, so that we could, as architects and citizens, understand a little more about how “invisible cities” are being built and must be preserved.